Beyond biopsychosocial: the keystone mechanism theory of pain - Lawn, Timothy; Sendel, Manon; Baron, Ralf; Vollert, Jan (Brain, behavior and immunity, 2023)
Pain is a deeply personal experience, with interindividual differences in its chronification and treatment presenting a formidable healthcare challenge. The biopsychosocial model (BPSm) has been hugely influential within nascent attempts at precision pain medicine, steering the field away from a reductionist biomechanical viewpoint and emphasising complex interactions of biological, psychological, and social factors which shape the individuality of pain. However, despite offering a strong theoretical foundation and holistic perspective, we contend that the BPSm remains limited in its capacity to deliver truly mechanistically informed treatment of pain. We therefore propose the keystone model of pain which offers a pragmatic balance between the dimensionality expansive BPSm and overly reductive approaches, providing both theoretical and practical advantages for the transition from treating populations to individual people.
Online verfügbar: 23. August 2023, Artikelversion: 27. August 2023
Gesehen am 11.09.2024